Internet: A Threat and Precaution - Hatua, Sudip Ranjan (Journal of Information and Knowledge, 2001)
Due to its versatile nature with low maintenance cost web is fast becoming the best medium of communication. Many academics now prefer Internet to publish their paper and many. journals and documents have online counterpart. With so much information available online, it is important to a researcher or scholars that their library provides them to access Internet. But this net access brings its own set of problems. The most dangerous problems are Internet threats, privacy and security. This paper is an effort to show what are the common threats we may face every moment and to avoid those what are the basic precautions we should follow to protect our system, database and important files.